2009
DOI: 10.1175/2008jcli2241.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tropical Easterly Waves and Precipitation during the North American Monsoon

Abstract: Relationships between tropical easterly waves (TEWs) and precipitation over Mexico and the United States are examined during the North American monsoon (NAM). The National Centers for Environmental Prediction-National Center for Atmospheric Research reanalysis data are used to identify 137 TEWs that cross Mexico north of 208N after monsoon onset over a 31-yr period from 1975 to 2005. Mean precipitation anomalies over two-day periods both before and after TEW passage are determined using Climate Prediction Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 45 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…This kind of mechanism is not uncommon in latitudes of Nayarit (Zuidema et al, 2007). The propagation of easterly waves, that could be associated with strong vertical coupling from diabatic heating, from across the tropical Atlantic to the eastern Pacific also affect precipitation patterns over parts of western Mexico (Giovannettone and Barros, 2008;Ladwig and Stensrud, 2009). Interactions between terrain heating and synoptic-scale disturbances not necessarily associated with NAM could also play an important role in explaining the temporal variability of precipitation in central and southern Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of mechanism is not uncommon in latitudes of Nayarit (Zuidema et al, 2007). The propagation of easterly waves, that could be associated with strong vertical coupling from diabatic heating, from across the tropical Atlantic to the eastern Pacific also affect precipitation patterns over parts of western Mexico (Giovannettone and Barros, 2008;Ladwig and Stensrud, 2009). Interactions between terrain heating and synoptic-scale disturbances not necessarily associated with NAM could also play an important role in explaining the temporal variability of precipitation in central and southern Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…The positive anomaly associated with the surge then moves north along the western Mexican coastline as the surge progresses, reaching northwestern Mexico by the time the surge arrives in Yuma and the southwestern United States in the subsequent days. Despite the long-held belief that surges are associated with enhanced regional mean NAM precipitation, recent work by Ladwig and Stensrud (2009) showed that surge events might redistribute NAM precipitation within the domain rather than enhance it.…”
Section: Introductionmentioning
confidence: 97%
“…Here, we examine the environmental factors contributing to the southward shift in TD wave tracks, with a focus on the eastern Pacific, where shifts in the wave tracks have implications with respect to cyclogenesis through interactions of the flow with the topography of Central America (Zehnder et al 1999;Molinari et al 2000). A southward shift in these waves could also have implications for seasonal rainfall patterns over Central America, Mexico, and the southwestern United States (Amador et al 2006;Adams and Stensrud 2007;Ladwig and Stensrud 2009;Seastrand et al 2015).…”
Section: Introductionmentioning
confidence: 99%